MISS WORLD DALAM KAJIAN FILSAFAT ILMU - Suyahmo, Suyahmo (Forum Ilmu Sosial, 2013)
Miss World, ontologically substantial, emphasizing the value of beauty, and this beauty are universal values, in which every person, especially women always crave the beauty value. When the value of beauty actualized in the geographic region of Indonesia, by itself can not be separated from the standard values and norms, standards prevailing philosophy and ideology. The existence of this standard philosophy and ideology, gave birth to a difference in perception between the assesment that agree and disagree Miss World was held in Indonesia. Against such a distinction, though philosophically and ideologically considered not reflect the culture of the nation, but goverment policy that he had, at last Miss World still be held. These considerations, based on the more practical value, pragmatic interests, because this contest is deemed able to bring benefits to the nation, especially in terms of economy, tourism, and others.